Structural and electrical study of glycolipid thin films prepared by spin-coating technique / Ng Boon Ki - Ng , Boon Ki (2014)

(untitled)
This research study is focused on the effect of the branched alkyl chain length to the structural and electrical properties of maltoside glycolipids. A theoretical model had been applied to the system to determine the bilayer molecular length of molecules from the hopping mechanism in the diffusion process. The initial research is related to the device fabrication of glycolipids. The glycolipids thin films were prepared by spin-coating technique on aluminium deposited glass substrate. The aluminium electrode was deposited by thermal evaporation method as the top electrode. Therefore, the metal-insulator-metal (MIM) devices had been fabricated. The subsequent research is on the study of the structural properties of glycolipids by experimental technique including optical polarizer microscopy, differential scanning calorimetry, thermogravimetry, Fourier transforms infrared spectroscopy, and x-ray diffraction. The optical polarizer microscopy and differential scanning calorimetry were used to identify the phase transition and the texture of the liquid crystalline. The thermogravimetry measurements were carried out to study the thermal stability of the glycolipid compounds. Subsequently, the Fourier transforms infrared spectroscopy was used to determine the functional groups which were present in the compounds at a specific wavenumber. Finally, the x-ray diffraction was used to infer the structural arrangement of the compounds based on the prominent peak which was observed in the x-ray diffraction pattern. The study on the electrical properties of glycolipids which were described in dielectric, conductivity and pyroelectric is also conducted. The dielectric and conductivity properties of glycolipid compounds have been studied in a broad frequency range (10-2 – 106 Hz) with varying temperature during heating and cooling processes. The spectra of the complex dielectric and conductivity for the glycolipid compounds have been fitted using empirical functions to analyze the polarization behaviour and the activation energy which were used to depict the phase transition behaviour. In addition, the dielectric constant at 100 Hz of glycolipid compounds has been extracted to study the phase transition behaviour. The pyroelectric effect of glycolipid compounds were investigated in several temperature ranges. The different length of branched alkyl chain influences the net dipole moment which contributes to the pyroelectric coefficient. In addition, the arrangement of molecules affects the dielectric loss and the figure-of-merit of the glycolipids thin films. Investigation on the diffusion process of glycolipid compounds was carried out at the final stage of this research. The charge carriers were diffused randomly around the polar sugar head group and were modeled by random walk scheme. From this model, the hydrogen bond lengths and bilayer molecular thickness of Malto-C12C8 were calculated as 2.45 Å and 3.61 nm respectively. Whereas, the hydrogen bond lengths and bilayer molecular thickness of Malto-C14C10 were calculated as 2.66 Å and 4.02 nm respectively.